Easy tuning of nanotexture and N doping of carbonaceous particles produced by spark discharge. (October 2021) - Alfè, M.; Gargiulo, V.; de Luca, O.; Rudolf, P.; Zhang, B.; Sabia, P.; De Joannon, M.
Highlights: N incorporation in spark discharge-generated c particles depends on N2 dilution gas purity. Pyrrolic-N, graphitic n and N-oxide groups are present for N2 as dilution gas. The spark frequency has no obvious influence on the c particle nanostructure. With N2 as dilution gas c particles exhibit smooth surfaces and more extended graphene sheets. Gas purity and spark discharge frequency affect the c particles' thermal behavior. Abstract: A better understanding of the effects of carbonaceous particulates in air pollution on human health and on the transmission of viruses requires studies with artificially produced aerosols that mimic the real ones. To produce such aerosols, methods to precisely tailor the morphology as well as the physical and chemical properties of carbon-based nanomaterials are crucial. Here we describe a facile and flexible approach to produce carbon-based nanoparticles with tailored N content by spark discharge utilizing graphite rods. Carbon-based nanoparticles with different nanotexture and N doping could be obtained by simply changing dilution gas (nitrogen, argon) and dilution gas purity (99 and 99.999%). The effect of the discharge frequency (50, 300 Hz) was also explored. The carbon-based nanoparticles were characterized by Fourier transform infrared and X-ray photoelectron spectroscopy, thermogravimetric analysis, and transmission electron microscopy. We find that the nanotexture is strictly linked to the chemical reactivity and to the surface chemistry. The use of N2 as dilution gas allowed for the incorporation of significant amounts of nitrogen (5–7 wt.%) in the carbonaceous particle network mainly as pyrrolic N, graphitic N and N-oxide functional groups. Graphical abstract: Image, graphical abstract